Pelvic Limb Amputation in a Giant Anteater (Myrmecophaga tridactyla) Traumatized by an Agricultural Harvester - Zupirolli, Guilherme Costa dos Santos; Cruvinel, Ciro Alexandre; Padula, Karina; Rosa, Milena Martins Carvalho; Zupirolli, Luana Alexandre Pimentel; Pala, Eduardo Kfouri; Cruvinel, Tatiana Morosini de Andrade; Santos, Jaqueline França dos (Acta Scientiae Veterinariae, 2021)
Background: The giant anteater (Myrmecophaga tridactyla) returned to the category of vulnerable by the 2014 IUCN / SSC, due to the population reduction, less than 30%. The main reasons are: environmental degradation and fragmentation, being run over, burning, attacks by hunting dogs, illegal trade and diseases. It is very common to find these fractured patients and the treatment is mostly surgical. Amputation is indicated when there are extensive lacerations and when reconstructive surgery is not possible. The objective is to report a viable treatment option in fractured wild patients, contributing to the preservation of the species. Case: It was received at the Veterinary Hospital Dr. Halim Atique - UNIRP an young female giant anteater (M. tridactyla) weighing 5.75 kg, brought by the Environmental Forestry Police of the municipality of São José do Rio Preto - SP, found in the region of Olímpia at a gas station. The animal was traumatized by an agricultural harvester, with partial traumatic amputation in the left pelvic limb and tail. In the preoperative period, the patient was admitted to hospital under assisted care, analgesia and all the necessary support for stabilization. High amputation was performed, with hip disarticulation and treatment of the tail wound, which was initially opted for healing in the first intention, where sutures were used to approach the edges of the wound, but presented dehiscence and was treated as a second intention. There were almost 2 months of care with specific food, cleaning of the enclosures, medications and dressings. After 57 days of hospitalization, the patient was transferred to the Municipal Zoo of São José do Rio Preto - SP, where it was moved to a larger and ideal enclosure for the species, with other giant anteaters also rescued. Discussion: The rate of complex fractures in accidents with wild animals is high. Amputations are indicated for patients with extensive lacerations without possible reconstructions, the patient in the present study had partial amputation of the limb, and reconstruction was impossible. The amputation technique of choice was disarticulation of the hip, as it is important that the patient does not try to support the limb, to avoid further trauma. The adaptation of animals to amputation is satisfactory, however, it should be noted that these individuals must remain under observation in the postoperative period, must remain confined to small rooms to avoid complications such as hemorrhage, seroma, dehiscence and infection of the surgical wound. The multidisciplinary team specialized in the required areas must be trained for this type of service. Adaptation to the new hospital environment, adaptation without an amputated limb, different food from that found in nature, daily handling for dressings and the movement of people in the sector are precautions that we must have for the success of the treatment. The great challenge for the recovery of traumatized wild patients is capture stress, transport to the operating room, lack of adaptation to the hospital environment and use of protocols that are unsuitable for the species, factors that can compromise the success of the treatment. Amputation can be a viable treatment alternative for fractured giant anteaters, when bone reconstruction is not possible. The amputation was performed successfully, providing another opportunity for this patient and contributing to the preservation of the species. Keywords: fracture, amputation, Myrmecophaga tridactyla, giant anteater.